Research on Factors Influencing National Budget Balance - Aivaras Senda; Ilona Skačkauskienė (Mokslas: Lietuvos Ateitis, 2014)
The article analyses factors influencing balance, explores importanceand significance of national budget. Firstly, to achieve thegoal, the conception of national budget is presented and mainfunctions are excluded. Thereinafter, the article examines nationalbudget revenues, their sources and national budget expensesand their classification. The correlation is accomplished, aimingto establish whether exists dependence of Lithuanian nationalbudget balance on the other factors. The analysis revealed that2 examined factors – level of unemployment and state debt –have hold over national budget balance.